5.4.18 Problems 1701 to 1800

Table 5.449: Second ODE homogeneous ODE

#

ODE

Mathematica

Maple

9924

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9925

\[ {}x y^{\prime \prime }+\left (x -6\right ) y^{\prime }-3 y = 0 \]

9926

\[ {}x^{4} y^{\prime \prime }+\lambda y = 0 \]

9927

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-25\right ) y = 0 \]

9928

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (36 x^{2}-\frac {1}{4}\right ) y = 0 \]

9929

\[ {}x^{2} y^{\prime \prime }+\left (x^{2}-2\right ) y = 0 \]

9930

\[ {}x y^{\prime \prime }+3 y^{\prime }+x^{3} y = 0 \]

9931

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9932

\[ {}16 x^{2} y^{\prime \prime }+32 x y^{\prime }+\left (x^{4}-12\right ) y = 0 \]

9933

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = 0 \]

9934

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

9935

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9936

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9937

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

9938

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+30 y = 0 \]

9939

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9940

\[ {}x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

9941

\[ {}2 x \left (x -1\right ) y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

9942

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 x y = 0 \]

9943

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

9944

\[ {}x^{2} y^{\prime \prime }+6 x y^{\prime }+\left (4 x^{2}+6\right ) y = 0 \]

9945

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

9946

\[ {}x \left (1-x \right ) y^{\prime \prime }+\left (\frac {1}{2}+2 x \right ) y^{\prime }-2 y = 0 \]

9947

\[ {}4 \left (t^{2}-3 t +2\right ) y^{\prime \prime }-2 y^{\prime }+y = 0 \]

9948

\[ {}2 \left (t^{2}-5 t +6\right ) y^{\prime \prime }+\left (2 t -3\right ) y^{\prime }-8 y = 0 \]

9949

\[ {}3 t \left (t +1\right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

9950

\[ {}x^{2} y^{\prime \prime }+\frac {\left (x +\frac {3}{4}\right ) y}{4} = 0 \]

9951

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (x^{2}-1\right ) y}{4} = 0 \]

9952

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

9953

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

9954

\[ {}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0 \]

9955

\[ {}x^{2} \left (-x^{2}+1\right ) y^{\prime \prime }+2 x \left (-x^{2}+1\right ) y^{\prime }-2 y = 0 \]

9956

\[ {}2 x y^{\prime \prime }+\left (x -2\right ) y^{\prime }-y = 0 \]

9957

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9958

\[ {}y^{\prime \prime }+2 x^{2} y^{\prime }+\left (x^{4}+2 x -1\right ) y = 0 \]

9959

\[ {}u^{\prime \prime }+2 u^{\prime }+u = 0 \]

9960

\[ {}u^{\prime \prime }-\left (2 x +1\right ) u^{\prime }+\left (x^{2}+x -1\right ) u = 0 \]

9961

\[ {}y^{\prime \prime }+2 y^{\prime }+\left (1+\frac {2}{\left (1+3 x \right )^{2}}\right ) y = 0 \]

9962

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9963

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}-\frac {2 y}{\left (1+x \right )^{2}} = 0 \]

9964

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9965

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9966

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9967

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9968

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9969

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9970

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9971

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9972

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9973

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9974

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9975

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9976

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }-x y = 0 \]

9977

\[ {}x^{2} y^{\prime \prime }+\left (3 x^{2}+2 x \right ) y^{\prime }-2 y = 0 \]

9978

\[ {}2 x^{2} \left (x^{2}+x +1\right ) y^{\prime \prime }+x \left (11 x^{2}+11 x +9\right ) y^{\prime }+\left (7 x^{2}+10 x +6\right ) y = 0 \]

9979

\[ {}x y^{\prime \prime }+\left (1+x \right ) y^{\prime }+2 y = 0 \]

9980

\[ {}x^{2} \left (x^{2}-2 x +1\right ) y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+\left (x +4\right ) y = 0 \]

9981

\[ {}2 x^{2} \left (x +2\right ) y^{\prime \prime }+5 x^{2} y^{\prime }+\left (1+x \right ) y = 0 \]

9982

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9983

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9984

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }-\left (x^{2}+\frac {5}{4}\right ) y = 0 \]

9985

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9986

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+4 x^{4} y = 0 \]

9987

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

9988

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

9989

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9990

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 0 \]

9991

\[ {}y^{\prime \prime } = 0 \]

9992

\[ {}y^{\prime \prime } = \frac {2 y}{x^{2}} \]

9993

\[ {}y^{\prime \prime } = \frac {6 y}{x^{2}} \]

9994

\[ {}y^{\prime \prime } = \left (-\frac {3}{16 x^{2}}-\frac {2}{9 \left (x -1\right )^{2}}+\frac {3}{16 \left (x -1\right ) x}\right ) y \]

9995

\[ {}y^{\prime \prime } = \frac {20 y}{x^{2}} \]

9996

\[ {}y^{\prime \prime } = \frac {12 y}{x^{2}} \]

9997

\[ {}y^{\prime \prime }-\frac {y}{4 x^{2}} = 0 \]

9998

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

9999

\[ {}y^{\prime \prime }+\frac {y}{x^{2}} = 0 \]

10000

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+y^{\prime }+y = 0 \]

10001

\[ {}\left (x^{2}-x \right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

10002

\[ {}x^{2} \left (-x^{2}+2\right ) y^{\prime \prime }-x \left (4 x^{2}+3\right ) y^{\prime }+\left (-2 x^{2}+2\right ) y = 0 \]

10003

\[ {}y^{\prime \prime } = \frac {\left (4 x^{6}-8 x^{5}+12 x^{4}+4 x^{3}+7 x^{2}-20 x +4\right ) y}{4 x^{4}} \]

10004

\[ {}y^{\prime \prime } = \left (\frac {6}{x^{2}}-1\right ) y \]

10005

\[ {}y^{\prime \prime } = \left (\frac {x^{2}}{4}-\frac {11}{2}\right ) y \]

10006

\[ {}y^{\prime \prime } = \left (\frac {1}{x}-\frac {3}{16 x^{2}}\right ) y \]

10007

\[ {}y^{\prime \prime } = \left (-\frac {3}{16 x^{2}}-\frac {2}{9 \left (x -1\right )^{2}}+\frac {3}{16 \left (x -1\right ) x}\right ) y \]

10008

\[ {}y^{\prime \prime } = -\frac {\left (5 x^{2}+27\right ) y}{36 \left (x^{2}-1\right )^{2}} \]

10009

\[ {}y^{\prime \prime } = -\frac {y}{4 x^{2}} \]

10010

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

10011

\[ {}x^{2} y^{\prime \prime } = 2 y \]

10012

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0 \]

10013

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

10014

\[ {}\left (x -2\right )^{2} y^{\prime \prime }-\left (x -2\right ) y^{\prime }-3 y = 0 \]

11011

\[ {}y^{\prime \prime } = 0 \]

11012

\[ {}y^{\prime \prime }+y = 0 \]

11016

\[ {}y^{\prime \prime }-y = 0 \]

11019

\[ {}y^{\prime \prime }+l y = 0 \]

11020

\[ {}y^{\prime \prime }+\left (a x +b \right ) y = 0 \]

11021

\[ {}y^{\prime \prime }-\left (x^{2}+1\right ) y = 0 \]

11022

\[ {}y^{\prime \prime }-\left (x^{2}+a \right ) y = 0 \]

11023

\[ {}y^{\prime \prime }-\left (a^{2} x^{2}+a \right ) y = 0 \]

11024

\[ {}y^{\prime \prime }-c \,x^{a} y = 0 \]